2004
DOI: 10.1098/rstb.2004.1524
|View full text |Cite
|
Sign up to set email alerts
|

Environmental causes for plant biodiversity gradients

Abstract: One of the most pervasive patterns observed in biodiversity studies is the tendency for species richness to decline towards the poles. One possible explanation is that high levels of environmental energy promote higher species richness nearer the equator. Energy input may set a limit to the number of species that can coexist in an area or alternatively may influence evolutionary rates. Within flowering plants (angiosperms), families exposed to a high energy load tend to be both more species rich and possess fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 115 publications
(135 reference statements)
4
55
0
Order By: Relevance
“…To date, results have been mixed, for example, Cardillo et al [72,73] and Ricklefs [74] reported faster rates of diversification at lower latitude in birds, but Wiens et al [75] [77,78]. Area by far explains the most variation in diversification models for plants [79][80][81], but significant additional variation in rates is explained by environmental energy [80,82].…”
Section: Diversity and Diversificationmentioning
confidence: 89%
“…To date, results have been mixed, for example, Cardillo et al [72,73] and Ricklefs [74] reported faster rates of diversification at lower latitude in birds, but Wiens et al [75] [77,78]. Area by far explains the most variation in diversification models for plants [79][80][81], but significant additional variation in rates is explained by environmental energy [80,82].…”
Section: Diversity and Diversificationmentioning
confidence: 89%
“…The amount of energy input into a system may limit the number of species that coexist in an area or influence evolutionary rates. Davies et al (2004) demonstrate that angiosperm families that are exposed to a high-energy load tend to be both more species rich and possess faster evolutionary rates, although it is not known whether one drives the other. They also highlight the case of Iridaceae, which demonstrates that the effects of the environment can vary among lineages.…”
Section: Why Are Some Biomes More Species Rich?mentioning
confidence: 99%
“…The final paper (Davies et al 2004) takes a different approach and asks why some biomes contain more species. There may be contemporary ecological explanations for this phenomenon in that different biomes may allow differing numbers of species to coexist.…”
Section: Why Are Some Biomes More Species Rich?mentioning
confidence: 99%
See 2 more Smart Citations